Constructing Qur'anic Personality in Tere Liye's Janji: A Critical Discourse Analysis through Van Dijk's Socio-Cognitive Framework - Kholisah Mardhiyah; Muhammad Yusuf (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study examines how Qur'anic personality is discursively constructed in Tere Liye's novel Janji and clarifies its relevance to Islamic Religious Education (PAI). It moves beyond identifying religious values to explain how language, narrative organisation, cognition, and social context produce a model of Muslim moral identity. The study employed a qualitative interpretive design using Teun A. van Dijk's socio-cognitive Critical Discourse Analysis. The complete novel constituted the primary corpus, while narrative passages, dialogues, character actions, and episodes served as analytical units. Data were coded using Nawawi's indicators of Qur'anic personality and examined through macrostructure, superstructure, microstructure, social cognition, and social context. Credibility was supported by theoretical and source triangulation, intercoder checking, reflexive memos, and an audit trail. Qur'anic personality is constructed through three mutually reinforcing relationships: with Allah, the self, and other people. Faith, tawakkul, gratitude, repentance, and steadfastness provide spiritual orientation; patience, courage, intelligence, optimism, and emotional regulation form ethical self-governance; and honesty, trustworthiness, democratic attitudes, care, and generosity translate morality into social responsibility. These dimensions operate dynamically through conflict, reflection, transformation, and prosocial action. The study integrates Nawawi's normative typology with van Dijk's socio-cognitive framework and proposes a relational-discursive model comprising spiritual anchoring, ethical self-governance, and social responsibility. It advances Islamic literary and discourse studies by explaining how Qur'anic identity is legitimised through narrative and offers a critical foundation for using fiction as a contextual, supplementary PAI resource for reflective moral and character education without claiming untested effects on students' character development outcomes.